2019
DOI: 10.1177/0891988719853046
|View full text |Cite
|
Sign up to set email alerts
|

Normative Data for the Montreal Cognitive Assessment in Greek Older Adults With Subjective Cognitive Decline, Mild Cognitive Impairment and Dementia

Abstract: Montreal Cognitive Assessment (MoCA) is among the most commonly used screening tools worldwide. Objective: The aim of the study was to provide normative data for the MoCA in a Greek cohort of people older than 60 years who meet criteria for subjective cognitive decline (SCD), mild cognitive impairment (MCI), or dementia in order to optimize cutoff scores for each diagnostic group. Method: Seven hundred forty-six community-dwelling older adults, visitors of the Day Center of Alzheimer Hellas were randomly chose… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
44
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 51 publications
(49 citation statements)
references
References 56 publications
0
44
1
Order By: Relevance
“…The analysis which was carried out based on the presence of the APOEε4 allele, a well-known risk factor for ΑD, showed similar improvement of the functional fitness variables in ε4-carriers and non-ε4-carriers of the Active group. These findings deviate from what is known so far regarding the questionable benefit of cognitive or combined exercise on the MCI APOEε4-carriers cognitive performance has been shown [24] . On the other hand, Passive non-ε4-carriers improved only in one task whereas Passive ε4carriers did not improve at all.…”
Section: Discussioncontrasting
confidence: 99%
“…The analysis which was carried out based on the presence of the APOEε4 allele, a well-known risk factor for ΑD, showed similar improvement of the functional fitness variables in ε4-carriers and non-ε4-carriers of the Active group. These findings deviate from what is known so far regarding the questionable benefit of cognitive or combined exercise on the MCI APOEε4-carriers cognitive performance has been shown [24] . On the other hand, Passive non-ε4-carriers improved only in one task whereas Passive ε4carriers did not improve at all.…”
Section: Discussioncontrasting
confidence: 99%
“…Our study aimed to add more clinical value in the previous studies [ 13 , 14 ] conducted in Greece about MoCA’s utility in clinical practice, by providing data mainly from a rural population of Northern eastern Greece, recruiting the study under a strict diagnostic protocol.…”
Section: Discussionmentioning
confidence: 99%
“…The sample of the study consisted of participants in urban centers. The second study, in 2019 [ 14 ], dealt with individuals who mentioned subjective cognitive complaints, people with MCI, and demented patients. The participants of this research were adults over 60 years of age from the urban city of Thessaloniki, a city in Northern Greece.…”
Section: Introductionmentioning
confidence: 99%
“…In our study, our results showed that all the R4Alz subtasks are free of education and gender effects, except for the WM component of short-term store, which seems to be affected by gender. As far as the gender effects on cognitive performance is concerned, there is controversy, with some studies indicating that gender does not usually affect the performance on cognitive tests [17,39], while others support the idea that gender differences in favor of males is a common finding and specifically in cognitive areas of verbal and visual spatial abilities [40][41][42]. These differences that are noticed among the genders in visual-spatial abilities reflect differences on the strategies that the two genders use [43].…”
Section: Gender and Educational Level Effectsmentioning
confidence: 99%
“…Currently, besides the fact that several neuropsychological tests were developed to capture as soon as possible cognitive decline related to AD, they are usually affected either from the means of the test administration (e.g., tablets or PCs, that older adults are not familiar to their use) [16], or they are education dependent [17]. Moreover, it seems that they are not able to differentiate between cognitively healthy lifespan development and SCD [18].…”
Section: Introductionmentioning
confidence: 99%